Knowing-with-snow in an outdoor kindergarten - Pernille Bartnæs; Anne Myrstad (Cappelen Damm Akademisk NOASP, 2022)
This article highlights how reciprocal relationships between children and the environment can contribute to exploring understanding of children's learning in the outdoor environment. We draw on data from a kindergarten in the northern part of Norway, where we have carried out fieldwork three hours a week from October to mid-May. During this period, the outdoor area was covered with snow of varying qualities. Snow and weather conditions are included as elements in a relational understanding, in which the environment is understood as open and dynamic - an interaction between past and present, between geography, materiality, people and the 'more-than-human'. The learner and the environment are understood as an indivisible process, where different elements exercise a reciprocal influence on each other. Using Ingold's concept of correspondence, we explore how children learn by being within and with the world. The article is a contribution to creating a nuanced understanding of children's learning and the educator's role within an outdoor environment in kindergarten practice.